TINJAUAN YURIDIS TENTANG UPAYA-UPAYA HUKUM - Putra Halomoan Hsb (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
Authority prosecute a case is referred to as jurisdiction is often also referred to in practice is the competence of the judiciary. While the form of a lawsuit lawsuit contetiosa also called contentious.In handling cases referred to in the legislation (UUPKK) on dasaranya cases handled divided by two. Contentiosa lawsuit and the court handle the lawsuit volunteir. Contentiosa lawsuit is a lawsuit that contains a dispute between two or more parties. The process of dispute settlement in a lawsuit contentiosa occur with process supporting each other in the form of a lawsuit, the answer, replik, duplik. This type of lawsuit so called op tegenspraak which supports the objection of mutual judicial process. Unlike the circuitry lawsuit volunteir are the problems posed by such party does not contain a dispute, but only a request for the establishment of rights by a judge in court, and no defendant or an opponent whose role is to support the lawsuit filed.Broadly speaking, the legal classification is divided into two, namely public law and private law. Public law is a law that gives the role of the state as arbiter in total serve the public interest, in other words the area of public law talk about the function of the state. Whereas private law is a legal instrument governing bagamana the relationship between individuals in matters of personal interest. Therefore, the most striking difference between the area of public law and private law is the area of public law regarding the function of the state while private law concerning the interests of individuals.